Trends in emergency medicine resident procedural reporting over a 10‐year period. Issue 1 (5th February 2023) - Gottlieb, Michael; Jordan, Jaime; Krzyzaniak, Sara; Mannix, Alexandra; King, Andrew; Cooney, Robert; Fix, Megan; Shappell, Eric
Abstract: Background: Procedural competency is expected of all emergency medicine (EM) residents upon graduation. The ACGME requires a minimum number of essential procedures to successfully complete training. However, data are limited on the actual number of procedures residents perform and prior studies are limited to single institutions over short time periods. This study sought to assess the number of Key Index Procedures completed during EM residency training and evaluate trends over time. Methods: We conducted a retrospective review of graduating EM resident procedure logs across eight ACGME accredited residency programs over the last 10 years (2013–2022). Sites were selected to ensure diversity of program length, program type, and geography. All data from EM residents graduating in 2013–2022 were eligible for inclusion. Data from residents from combined training programs, those who did not complete their full training at that institution (i.e., transferred in/out), or those who did not have data available were excluded. We determined the list of procedures based upon the ACGME Key Index Procedures list. Sites obtained totals for each of the identified procedures for each resident upon graduation. We calculated the mean and 95% CI for each procedure. Results: We collected data from a total of 914 residents, with 881 (96.4%) meeting inclusion criteria. The most common procedures were point‐of‐care ultrasound, adult medical resuscitation, adult trauma resuscitation, and intubation. The least frequent procedures included pericardiocentesis, cricothyroidotomy, cardiac pacing, vaginal delivery, and chest tubes. Most procedures were stable over time with the exception of lumbar punctures (decreased) and point‐of‐care ultrasound (increased). Conclusions: In a national sample of EM programs, procedural numbers remained stable except for lumbar puncture and ultrasound. This information can inform residency training curricula and accreditation requirements.